Analisis Pengaruh Soda Carry Over Terhadap Kebutuhan Clo2 (Klorin Dioksida) Pada D0 Stage Bleaching Dissolving Pulp - Widya Kartika Sari Simbolon (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The bleaching process in dissolving pulp production is a crucial stage for achieving pulp with a high brightness level. One of the factors affecting the efficiency of this process is the presence of soda carry over or soda loss, which refers to residual alkali from the cooking process that is carried into the bleaching stage. This study aims to analyze the effect of soda carry over on the chlorine dioxide (ClO₂) requirement during the D₀ bleaching stage in the pulp industry. The research method involved the collection of bleaching process operational data, analysis of process parameters, and evaluation of the relationship between soda carry over, chlorine dioxide (ClO₂) consumption, and other supporting variables. The results indicate that an increase in soda carry over leads to higher chlorine dioxide (ClO₂) consumption due to neutralization reactions under alkaline pH conditions, thereby reducing the effectiveness of the bleaching process. Furthermore, soda carry over is influenced by several factors, including pulp washing efficiency, pulp consistency, and equipment operating conditions. Therefore, controlling soda carry over is essential for optimizing chemical consumption, improving bleaching process efficiency, and reducing production costs. This study recommends enhancing the washing stage efficiency and maintaining proper control of process parameters to minimize soda carry over.